Tydzień Akademika Wybrzeża (Gdynia : [s.n.], 1946)
Druk inf. o Tygodniu Akademika, który miał miejsce w Gdyni 17-24.11.1946 r.
Keywords: Szkoły -- Polska -- Gdynia -- 1945-1970.; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła